Structural changes of polyacrylonitrile fibers in the process of wet spinning. Issue 30 (8th January 2020) - Sun, Lihao; Shang, Lei; Xiao, Linghan; Zhang, Mengjie; Li, Ming; Ao, Yuhui
ABSTRACT: In this article, the structural changes of polyacrylonitrile (PAN) fibers at the key stages of wet spinning are systemically studied. According to the X‐ray diffraction and scanning electron microscopy analysis, the as‐spun fibers show a homogeneous three‐dimensional fibrillar network structure with random crystallite orientation, low crystallinity, and abundant pores. As the draw ratio increases, the crystallite orientation and crystallinity increase firstly in the skin and then in the core. The uneven force distribution in fiber is responsible for the inhomogeneous change of fibrillar network. According to the X‐ray scattering and scanning electron microscopy analysis, the size, shape, and volume fraction of pores are strongly dependent on the compactness degree of fibrillar network. As the fibrillar network inhomogeneously shrinks, the total pore volume decreases, and the volume fraction of small‐sized pores increased considerably from 25 to 96%, leaving a handful of large‐sized pores in the core. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48905. Abstract :